KONSEP ANALISIS SWOT DALAM PENINGKATAN MUTU LEMBAGA MADRASAH - Abdul Hadi (Universitas Islam Negeri Ar-Raniry, 2013)
Education is an important part of national development that determines nation’s economic growth. It also an investment in human resources development that improves ability as supporting factors in human life. In managing educational system, capacity is needed, especially by stake holder, from central, region until head master. Head master has a great role in managing educational system at school and teacher teach their students and organize learning activity effectively. Globalization forces the educational institution to prepare the students to deal with global changes. So that the student capable enough to be the agent of change from a positive angel. One of concept introduced by educational system to deal with the global change is SWOT analysis. SWOT is stand for Strength, Weakness, Opportunity and Thread.